2010
DOI: 10.1111/j.1750-3841.2010.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Lactate Effect on the Shelf Life of Osmotically Dehydrated Guavas

Abstract: The effect of calcium lactate on osmodehydrated guavas in sucrose and maltose solutions was monitored during storage under passive modified atmosphere for 24 d at 5 °C. Sample texture and color characteristics, microbial spoilage, sensory acceptance, structural changes, and gas composition inside the packages were periodically evaluated. Calcium lactate inhibited microbial growth on guavas, with yeast and mold counts in the order of 10(2) CFU/g throughout storage. The calcium salt reduced respiration rate of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Therefore, calcium lactate preserved melon structure, causing a strengthening of the cell wall along storage, but the salt was unable to avoid cellular plasmolysis. Similar behavior was pointed out by Pereira et al (2010) in their study with osmodehydrated guavas, using sucrose or maltose solutions containing calcium lactate.…”
Section: Light Microscopysupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, calcium lactate preserved melon structure, causing a strengthening of the cell wall along storage, but the salt was unable to avoid cellular plasmolysis. Similar behavior was pointed out by Pereira et al (2010) in their study with osmodehydrated guavas, using sucrose or maltose solutions containing calcium lactate.…”
Section: Light Microscopysupporting
confidence: 84%
“…OD+ coating and CaDIP +coating samples had lower microorganism growth along the storage period, showing yeast and mold counts about 10 5 CFU g −1 after 14 days of storage, meaning that the use of pretreatments combined with the application of pectin coatings promoted higher microbiological stability on fresh-cut melon. This behavior can be attributed to the antimicrobial effect of calcium lactate, as previously pointed out by Alandes et al (2006), Moraga et al (2009), andPereira et al (2010) in their works with minimally processed apple, grapefruit, and guava, respectively.…”
Section: Microbiological Analysismentioning
confidence: 55%
“…However, it has been reported that calcium lactate (Ca-L) has some different benefits from calcium chloride (CaCl 2 ) because it avoids the bitterness and off-flavour associated with the chloride salt (Luna-Guzm an & Barrett, 2000;Alandes et al, 2009) and also avoids the formation of carcinogenic compounds (chloramines and trihalomethanes) linked to the use of chlorine . Many studies reported that Ca-L has been used as a firming agent for various fruits such as cantaloupe (Luna-Guzm an & Barrett, 2000), peach (Manganaris et al, 2007), melon (Aguayo et al, 2008;Ferrari et al, 2010), grapefruit (Moraga et al, 2009), pear (Alandes et al, 2009) and guavas (Pereira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium reduces water vapor permeability in polysaccharide coatings and strengthens the structure and integrity of plant tissue. Calcium ions form bridges between the free carboxyl groups of the pectin chains forming complexes with the cell wall and middle lamella pectin, improving and promoting greater tissue firmness (Pereira et al, 2010). Gum arabic, which has the desired stabilizing, emulsifying, and binding properties, is one of the best-known natural gums.…”
Section: Hydrocolloids Used In Ec Preparationmentioning
confidence: 99%